Citizen science project’s contributions to species literacy for pre-service biology teacher - Ipin Aripin; Topik Hidayat; Nuryani Rustaman; Riandi Riandi (Universitas Ahmad Dahlan, 2022)
This study aims to describe the contribution of the Citizen Science Project (CSP) program to the species literacy of pre-service biology teachers. Using a quasi-experimental method with a Citizen Science (CS) approach, this study involved 82 participants from two campuses who were recruited voluntarily in two different projects. A total of 68 participants were involved in Project I (monitoring of insect pollinators of mango (Mangifera indica) inflorescence) and 14 participants were involved in Project II (monitoring of butterflies in citrus (Citrus amblycarpa) plantations). Species literacy test and a questionnaire were used as data collection instruments. The species literacy test consists of 14 items of species identification questions for Project I and 12 items of species identification questions for Project II. The questionnaire was used to determine the perception and evaluate the learning outcome (LO) of the CSP program. The data were analyzed statistically and described according to the research findings. The results showed that species literacy in pre-service biology teachers improved in the moderate category. Most participants perceived that the CSP program could improve knowledge, attitudes, and skills about species. The LO evaluation of the CSP program showed that the indicator of participants' interest in science and environment increased higher than the others. The program can be used as an alternative in increasing species literacy in the public.